Sajak Ladang Jagung Karya Taufiq Ismail: Kajian Semiotika Riffaterre - Annisa Mahdi; Muhammad Ismail Nasution (Departemen Bahasa dan Sastra Indonesia dan Daerah, 2022)
Literary works in Indonesia is developing quite rapidly. However, with this development the author can give a new touch in his work. One of the developing literary works is poetry, both in terms of its structure and meaning. Research objectives: (1) describe semantic indirection, (2) describe heuristic and hermeneutic readings (3) describe matriks, models, and variant, (4) and show the hypogram from the poems of Januari, 1949 by Taufiq Ismail. This research is included in the type of literary research using descriptive methods because the sources are books and journals. The data are in the form of words, phrases, clauses, and sentences from the Januari, 1949 poem by Taufiq Ismail. The sources of the data in this study were the poems in the book Sajak Ladang Jagung by Tufiq Ismail which was published by Pustaka Jaya. The data collection technique used is recording. The findings of this study are (1) semantic indirection, (2) heuristic and hermeneutic reading, (3) matriks, models, variant and, (4) hypogram from Taufiq Ismail’s Januari, 1949 poem.